Design and Construction of Smart House Prototype Based Internet of Things (Iot) Using Esp8266 - Adi Winarno; Mahfud Affandi (BEST, 2022)
IoT (Internet of Things) is a concept that aims to expand the benefits of continuously connected internet connectivity continuously. IoT can be used at home as a smart home system for controlling electronic equipment that can be operated by means ofinternet connection (WiFi). This IoT-based smart home system uses ESP 8266 microcontroller as hardware and blynk application as a tool controller and control. This system consists of a lamp controller, knowing humidity and room temperature, detection of human movement at home abandoned, early detection of fire sources to prevent house fires, and LPG gas leak detector for home security. There are four sensors used are PIR sensors to detect human movement, MQ2 sensor to detect LPG gas leaks, flame sensor to detect LPG gas leaks early detection of fire, and the DHT11 sensor to determine humidity and temperature. The design of this system uses a relay which is used as a liaison lamp with system.